2011
DOI: 10.1103/physrevd.83.074506
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of quark propagators from twisted-mass lattice QCD atNf=2

Abstract: We present results concerning the non-perturbative evaluation of the renormalisation constant for the quark field, Z q , from lattice simulations with twisted mass quarks and three values of the lattice spacing. We use the RI'-MOM scheme. Z q has very large lattice spacing artefacts ; it is considered here as a test bed to elaborate accurate methods which will be used for other renormalisation constants. We recall and develop the non-perturbative correction methods and propose tools to test the quality of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…All together, these results appear to be fairly consistency. A similar consistency has also been found when comparing the condensate extracted from the lattice quark propagator and the Taylor coupling with N f ¼ 2 dynamical flavors [24,36]. Still, despite this consistency and the rather convincing estimate of à QCD obtained with the good agreement of the OPE formula and the lattice results for the Taylor coupling with N f ¼ 2 þ 1 þ 1, the actual nature of the unavoidable nonperturbative corrections and the condensates involved is a controversial matter.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…All together, these results appear to be fairly consistency. A similar consistency has also been found when comparing the condensate extracted from the lattice quark propagator and the Taylor coupling with N f ¼ 2 dynamical flavors [24,36]. Still, despite this consistency and the rather convincing estimate of à QCD obtained with the good agreement of the OPE formula and the lattice results for the Taylor coupling with N f ¼ 2 þ 1 þ 1, the actual nature of the unavoidable nonperturbative corrections and the condensates involved is a controversial matter.…”
Section: Introductionsupporting
confidence: 65%
“…The rhs of Eq. (3) stands for the definition of c WMS 2 in the ''Wilson MS'' scheme 3 (MS) [36], after the introduction of c MOM 0 ðp 2 ; 2 Þ ¼ À pert ðp 2 ; " À1 Þ À pert ð 2 ; " À1 Þ ; (5) which allows one to recast Eq. (1) to read…”
Section: A Two-point Functionsmentioning
confidence: 99%
“…However our previous studies in quenched approximation suggested that such universality (even including the three-gluon vertex) is indeed compatible with the numerical data (N f =0) [20,27,28,6,29,7]. This has been also supported by the calculations with N f =2 dynamical flavours [19,30]. Now we will address this question in the N f =2+1+1 case, to clarify the nature itself of the unavoidable nonperturbative corrections and the involved condensates.…”
Section: Introductionmentioning
confidence: 64%
“…As we did in ref. [17,18,30] for the Taylor coupling and the vector quark propagator, the gluon propagator renormalization constant Z Latt 3 in MOM scheme can be written as…”
Section: Testing the Opementioning
confidence: 99%
“…For instance, the study of the coupling defined from the asymmetric ( MOM) three-gluon vertex and estimated from quenched lattice data revealed the main role of nonperturbative power corrections to account for its running [16]. Then, in a vast series of papers [17,18,[22][23][24][25][26][27][28][29][30], some of us have exhaustively proven that Wilson's Operator Product Expansion (OPE) provides a general framework to include non-perturbative contributions, and that its application to QCD couplings for several renormalization schemes allows a coherent and simple explanation of the running obtained from the lattice for momenta as…”
Section: Summary and Conclusion 12mentioning
confidence: 99%